Voltage Flickering Reduction Using Distribution STATCOM - Yahia M Esmail; S K Elsayed; M A Mehanna (Institute of Advanced Engineering and Science, 2016)
Power Quality is becoming intensity concerned from both electric utilities and customers. Voltage Flicker is a major power quality problem as it has a significant impact on both the equipment and production environment. This work describes the voltage control technique of reduction of voltage flicker and clearing fault using Distribution Static Synchronous Compensator (DSTATCOM). The test system used is IEEE 9-bus distribution system clarified the optimal location of DSTATCOM by using Artificial Neural Network. A simulation was done using MATLAB/Simulink software.